Pengaruh Budaya Dan Disiplin Kerja Terhadap Kinerja Personel Polres Pelabuhan Di Makassar - Budy, Setya; Syam, Andi Hendra; Yunus, Muh (STIM-LPI Makassar, 2025)
The aim of this research is to determine and analyze the influence of culture and work discipline on the performance of Port Police Personnel in Makassar. This research uses quantitative methods to assess the influence of work culture and work discipline on the performance of port police personnel in Makassar. Data was obtained from 147 personnel using questionnaires and primary and secondary data sources. Data analysis used IBM SPSS Statistics Version 25.0, including classical assumption tests and multiple linear regression to evaluate the influence of variables. The research results show that work culture has a positive and significant effect on personnel performance, work discipline has a positive and significant relationship with personnel performance and work culture and work discipline together have a significant effect on personnel performance. For research suggestions, to maintain work culture and work discipline among personnel, you can create and implement a reward or incentive system as a form of appreciation for employees who consistently show high commitment to work culture and work discipline. Reward systems may include bonuses, public recognition, or opportunities for career development as additional forms of motivation for dedicated Personnel.